Patterned Ga2O3 for current blocking and optical scattering in visible light‐emitting diodes. Issue 10 (17th June 2016) - Kim, Seung Hwan; Lee, Keon Hwa; Park, Hyun Jung; Shervin, Shahab; Asadirad, Mojtaba; Lee, Sung‐Nam; Kwak, Joon Seop; Ryou, Jae‐Hyun
Abstract : Patterned gallium oxide (Ga2 O3 ) using one‐step patterning followed by oxygen plasma treatment on a p‐GaN layer can function as both current‐blocking and optical‐scattering regions for uniform current spreading and improved light‐extraction efficiencies. The results showed that the optical output power of the LED with patterned Ga2 O3 increased by 16.8% at 60 mA compared to that of conventional LEDs. Numerical studies on light tracing and emission pattern, and external quantum efficiency evaluation support the improvement of both uniform current spreading and light‐extraction efficiencies by patterned Ga2 O3 .